Kajian Fraksi Air Terikat Primer, Sekunder dan Tertier dalam Kelapa (Cocos nucifera L.) - Rita Hayati (Jurnal Agrista, 2010)
Study of The Primary bound Water Fraction, Secondary and Tertiery in Coconut (Cocos nucifera L.)ABSTRACT. Critical moisture and water activity of coconut (Cocos nucifera L.), were analyzed for the first and second critical points of transition among the primary, secondary and the tertiery  bound water fraction in the coconut. It was found out that the first critical points of moisture content and water activity were Mp of 5.22% db and ap of 0.30 respectively. The second ctitical points were water content Ms 12.4% db and water activity as 67% respectively. Coconut sample in the primary bound water fraction (represented by moisture content at 5.22% db), was stable in colour and appearance, but slightly rancid due to molecular mobility of the liquid oil content. The sample in the secondary bound water fraction (represented 12.4% db), has a colour change to darker brown, and in the tertiary bound water fraction (represented 90.5% db), mold growth appeared on the 12 days storage. Coconut indicated and Intermediate Moisture Food (IMF), because limited shelf life for few days at room temperature.